Emotional Intelligence as a Moderator of the Relationship Between Stress, Depressive Symptoms, and Job Performance - Binti Mat Nasir, Nor Aini; Abas, Nurul ‘Ain Hidayah (Humanitas: Indonesian Psychological Journal, 2024)
This study aims to examine the relationships between stress and depressive symptoms on job performance. The role of emotional intelligence (EI) was used to determine whether it has a moderating effect on relationships. Stratified sampling was utilized to select 282 secondary school teachers in Kelantan. Stress, depressive symptoms, EI, and job performance were measured using the Job Stress Scale, the Major Depression Inventory, the USM Emotional Quotient Inventory, and the Individual Work Performance Questionnaire 1.0, and all of these were translated back-to-back. Pearson correlation and multiple regression analysis methods were used to analized the data. The results indicated that there was a significant positive relationship between stress and job performance r = .169, while there was a significant negative relationship between depressive symptoms and job performance r = .-174. In addition, it found that there was no significant effect of EI on the relationships between stress and job performance (β =.08, p>0.05), as well as on the relationship between depressive symptoms and job performance (β =.03, p>.05). This study highlights the importance of reducing depressive symptoms among school teachers to maintain their performance and it suggests the school’s management to take proactive measures to support teachers’ mental well-being.